Work discipline as a behavioral mechanism linking work motivation and compensation to employee performance - Maudy Nur Arifianti; Wisnu Panggah Setiyono; Nur Ravita Hanun; Imashev Aibek Baduanovich (Jurnal Fokus Manajemen Bisnis, 2026)
Despite the existence of motivating and compensation systems, inconsistent work discipline frequently limits employee performance in local government entities. Using work discipline as a mediating variable, this study examines the direct and indirect effects of work motivation and compensation on employee performance. This study uses a convenience sample of 150 government personnel from 18 sub-district offices in Sidoarjo Regency, East Java, Indonesia. Partial least squares structural equation modeling was used to examine the data. The results show that work motivation and compensation significantly influence both work discipline and employee performance, while work discipline also directly affects employee performance. Work discipline acts as a key mediator in the relationships between work motivation, compensation, and employee performance. This study contributes to the development of theories in human resource management and organizational behavior, particularly by explaining the relationships among work motivation, compensation, work discipline, and employee performance. In practical terms, the findings of this study have important implications for government agencies, specifically subdistrict offices in Sidoarjo Regency, East Java, Indonesia, as they work to improve employee performance. Nevertheless, the cross-sectional design and single-district emphasis of this study are its limitations. Therefore, future research is recommended to test this model across different regions and organizational settings.